Function and Therapeutic Implications of tRNA Derived Small RNAs - Wilson, Briana; Dutta, Anindya (Frontiers in Molecular Biosciences, 2022)
tRNA derived small RNAs are mainly composed of tRNA fragments (tRFs) and tRNA halves (tiRs). Several functions have been attributed to tRFs and tiRs since their initial characterizations, spanning all aspects of regulation of the Central Dogma: from nascent RNA silencing, to post-transcriptional gene silencing, and finally, to translational regulation. The length distribution, sequence diversity, and multifaceted functions of tRFs and tiRs positions them as attractive new models for small RNA therapeutics. In this review, we will discuss the principles of tRF biogenesis and function in order to highlight their therapeutic potential.